Variasi Morfologis Bahasa Slang dalam Transkrip Podcast - Ramadhan, Genta; Liusti, Siti Ainim (Universitas Negeri Padang, 2024)
This research aims to: (a) to describe the morphological variations of the slang lexicon in podcast transcripts, and (b) to explain the process of forming these morphological variations. The research methodology used is descriptive in nature. Qualitative data obtained from the research is described based on the research objectives. The data sources for this research are the YouTube accounts of Volix media, HAS Creative, and Slap Show. The data collection technique involves several stages: (1) opening the YouTube social media application, (2) reviewing video transcripts from the Volix, HAS Creative, and Slap Show YouTube channels, (3) identifying data in the form of various slang terms found in the video transcripts, (4) documenting the data in a notebook. The data analysis technique consists of four stages: (1) identifying the collected data, (2) classifying the data based on the research objectives using a predefined format, (3) analyzing the classified data, and (4) formulating conclusions based on the analysis results. The research findings show that the slang lexicon used in the podcast transcripts can be categorized into two forms: (a) monomorphemic (68 instances), such as okay, spontaneous, shy, and ego, and (b) polymorphemic (57 instances), such as rupiah slave, baperan, and prepare. The formation of the slang lexicon in podcast transcripts involves several processes: (a) affixation (15 instances), such as complaining, ignya, and teasing, (b) reduplication (10 instances), such as guessing, carelessly, and saying goodbye, (c) composition (2 instances), such as rupiah slaves and hourly average, and (d) acronymization (18 instances), such as AC, VPN, and KTP.